THE STRUGGLE OF CATH AVERY AGAINST HER INTROVERT PERSONALITY ON FANGIRL BY RAINBOW ROWELL - Tarsila, Hersi Intan (LANTERN (Journal on English Language, Culture and Literature), 2016)
This thesis will analyze the main character of Fangirl by Rainbow Rowell, Cath Avery. The main purpose of this thesis is to analyze the intrinsic and extrinsic aspects of the story. In this thesis, the intrinsic aspects will use characters, characterizations, conflicts and settings and the extrinsic aspect will use Carl Gustav Jung’s Analytical Psychology Theory. The methods that are used in this thesis are the library research and psychological approach. The result of the analysis shows that Cath Avery’s personality is the form of introvert personality type. The cause of Cath Avery’s introvert personality can be seen from the external element. The introvert personality also influences Cath Avery having inferior feeling, feeling uncomfortable toward her surrounding and having trouble with her social life.